IMPACT OF SOCIAL MEDIA ON THINKING STYLE AMONG EARLY ADULTHOOD - Ms.Minakshi (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Early Adulthood is a stage is characterized by a variety of psychosocial and cognitive changes as individuals’ transition from adolescence to full-fledged adulthood the rapid rise of social media has significantly transformed how people communicate, share information, and interacts with one another. This study explores the impact of social media usage on thinking styles among individuals in early adulthood. Utilizing a sample of 92 college-going girls, the study employs quantitative measures to analyze, how age group influences by social media, how time spent on social media, the platforms used, social media facilitate learning, state of mind during social media usage, social media trigger thoughts processes and the purposes for its usage correlate with thinking styles. The results indicate a complex relationship between social media engagement and cognitive processes, with implications for mental health and personal development.